2011
DOI: 10.1177/0042098011417905
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Route to Owner-occupation: The Impact of Borrowing Constraints on Young Adult Homeownership Transitions in Britain in the 1990s

Abstract: The reduction in young adult homeownership rates in Britain in the 1990s was partly caused by demographics and partly by a shift in the income distribution. Most of their relative income deterioration occurred in the first part of the decade, yet young adult homeownership rates continued to fall. This paper extends that analysis by empirically examining whether lender-imposed borrowing restrictions also contributed to their decline, especially since house prices rose rapidly in the second half of the decade. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
0
34
0
1
Order By: Relevance
“…Although several British studies have examined the association between parental attributes and young people's housing trajectories, these relied on small samples gathered when a large proportion of households rented from Local Authorities (Jenkins & Maynard, 1983;Murphy, 1984;Payne & Payne, 1977). More recent nationally representative analyses have, by contrast, tended to use relatively short portions of panel data to examine parental effects on transitions in and out of the parental home or into homeownership (Andrew, 2012;Ermisch, 1999;Stone et al, 2014). These studies have shown how contextual forces shape young adults' housing transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several British studies have examined the association between parental attributes and young people's housing trajectories, these relied on small samples gathered when a large proportion of households rented from Local Authorities (Jenkins & Maynard, 1983;Murphy, 1984;Payne & Payne, 1977). More recent nationally representative analyses have, by contrast, tended to use relatively short portions of panel data to examine parental effects on transitions in and out of the parental home or into homeownership (Andrew, 2012;Ermisch, 1999;Stone et al, 2014). These studies have shown how contextual forces shape young adults' housing transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to data constraints, few studies have assessed whether the impacts of parental background have changed over time. Although cross-sectional data show that broader trends of declining homeownership and rising shared living in young adulthood are evident in Britain (Andrew, 2012;Stone et al, 2011), it is not clear whether family background stratifies these broad patterns. As welfare, labour market and housing systems shape young people's life courses we cannot assume that trends documented for the Netherlands (Smits & Mulder, 2008) and Sweden (Öst, 2012) apply equally to Britain.…”
Section: Introductionmentioning
confidence: 99%
“…Second, public debates about whether housing systems are entrenching and deepening social inequality mean that scholars are also becoming increasingly interested in how parental background shapes entry into homeownership (Coulter, 2018;Lersch & Luijkx, 2015;McKee, 2012). Concerns have been voiced that macrotrends such as the declining availability of secure well-paid work, greater indebtedness (often to fund higher education), reduced public welfare provision, and enhanced problems of housing access and affordability are all making it harder for young people to muster the resources to become homeowners (Andrew, 2012;Dewilde et al, 2018;Lennartz et al, 2016;Lersch & Dewilde, 2015). This could make transitions into owner-occupation increasingly contingent on parental financial transfers or other downward intergenerational flows of economic and practical support (Heath, 2018;Mulder & Smits, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, economic influences have been the major contributor to decision-making over the years. Among the prominent ones are consumer incomes (Andrew and Meen, 2003;Robst et al, 1999;Gathergood, 2011;Di Salvo and Ermisch, 1997); credit and affordability requirements (Quercia et al, 2003;Andrew, 2012). On the other hand, findings have also indicated demographic influences such as marriage, gender, race, norms, status, age and family as factors affecting tenure decisions (see Baddeley, 2011;Drew, 2014;Fu, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent trends and timing of tenure transitions show some well-established drivers contributing to housing tenure decision making (e.g. in Andrew (2012); Baddeley (2011); Ben-Shahar (2007)). To the best of the author's knowledge, no study has explored the impact of the duration of socialisation in parental housing on housing tenure decision among young adults in Britain.…”
Section: Introductionmentioning
confidence: 99%